(untitled) (Advances in Applied Mathematics and Mechanics, 2010)
The objectives of the present study are to investigate the effects of heat and mass transfer on the unsteady flow of a perfect conducting polar fluid over a flat sheet with a linear velocity in the presence of thermal radiation. Successive approximation method developed in Zakaria [Appl. Math. Comput. 10 (2002), Appl. Math. Comput. 155 (2005)] is adopted to solve the problem. The effects of Alfven velocity, mass transfer, various material parameters, Prandtl number, Schmidt number and relaxation time on the velocity, angular velocity, temperature and concentration are discussed and illustrated graphically.